2018
DOI: 10.1039/c8ra01061g
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive ethylene glycol-doped PEDOT–PSS organic thin films for LPG sensing

Abstract: In this study, for the first time we report the fabrication of low-cost ethylene glycol (EG)-doped PEDOT-PSS (poly 3,4-ethylenedioxythiophene:polystyrene sulfonate) organic thin film sensors for the detection of LPG at room temperature. The prepared thin films were characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible (UV-Vis) spectroscopy and thermogravimetric analysis (TGA) techniques for the analysis of their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…Further, the bright regions in the AFM image of pure PEDOT-PSS thin lm are assigned to highly conductive PEDOT content and the dark regions correspond to insulating PSS-rich domains. 35…”
Section: Scanning Electron and Atomic Force Microscopy (Sem/ Afm)mentioning
confidence: 99%
See 3 more Smart Citations
“…Further, the bright regions in the AFM image of pure PEDOT-PSS thin lm are assigned to highly conductive PEDOT content and the dark regions correspond to insulating PSS-rich domains. 35…”
Section: Scanning Electron and Atomic Force Microscopy (Sem/ Afm)mentioning
confidence: 99%
“…In our previous works, we have demonstrated that, the post treatment of PEDOT-PSS lms using polar organic solvents with high boiling points can signicantly enhance the conductivity of PEDOT-PSS aqueous dispersions by 2-3 orders of magnitude. [34][35][36][37] In this study ethylene glycol (EG) is used as a solvent for the post treatment to enhance the conductivity of pristine PEDOT-PSS and PEDOT-PSS/rGO nanocomposites. Post treatment of EG into PEDOT-PSS/rGO leads to phase segregation of PEDOT and PSS, reduces the coulombic interactions between PEDOT and PSS phases.…”
Section: Electrical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that the layout with thinner fingers actually helped to increase the parallel resistance of the sensors, but minimally modified their sensitivity. Moreover, as occurred with the capacitance of the sensors, in all cases, their sensitivity decreased as the frequency increased, due to the decrease in dielectric constant for both GO and PEDOT:PSS with respect to increasing frequency [46,48]. Furthermore, the highest sensitivity was obtained for an intermediate concentration of PEDOT:PSS since, although it helped to improve the sensitivity at higher RH values, if the concentration was too high, the performance of the sensors at low RH values As analyzed before, the changes in the impedance were ruled by the resistance behavior (see Figure 5).…”
Section: Capacitive Humidity Sensor Characterizationmentioning
confidence: 85%